Haridvāre Kumbhayoga o sādhu mahāsammilanī : 1321 sālera Haridvāra Kumbhayogera bistrta bibaraṇa - Yogānanda, Swami (Sārasvata granthābalī, 1968)
On the significance and importance of the Kumbh Mela, Hindu religious festival held every twelve years at Hardwar and description of the one held in 1915.